Analisis Nonlinier Tekuk Torsi Lateral pada Balok Baja Cellular - Hung, Benny Gunawan; Suryoatmono, Bambang (Department of Civil Engineering, Diponegoro University, 2019)
One of many buckling modes that could occur on the beam is lateral-torsional buckling. Lateral torsional buckling could result in lateral deformation and torsion of section. In the AISC 360-16 Spesification, an equation is provided to calculate lateral-torsional buckling critical moment of prismatic I section beam. For cellular beams (I section beam with circular openings), AISC Design Guide 31 states that the lateral-torsional buckling critical moment should be checked in accordance with AISC Specification using gross section properties. With this assumption, thus, the design guide ignores the existence of circular opening on the web, which can cause a reduction of lateral-torsional buckling critical moment. In this study, lateral-torsional buckling analysis on cellular beam with simple support loaded by distributed transversal load has been done - the analysis utilized finite element based software. From the analysis, the critical moment is lower than AISC 360-16 critical moment with the assumption of prismatic I section beam, with the maximum difference percentage of 43,58%. Based on this study, a correction factor has been obtained to estimate the critical moment of cellular beams by using equation on AISC 360-16.